Acute ischemic stroke triggers a cellular senescence-associated secretory phenotype - Coral Torres-Querol (Nature Portfolio, 2021)
Abstract Senescent cells are capable of expressing a myriad of inflammatory cytokines and this pro-inflammatory phenomenon is known as senescence-associated secretory phenotype (SASP). The contribution of this phenomenon in brain ischemia was scarce. A mouse model of transient focal cerebral ischemia by compressing the distal middle cerebral artery (tMCAo) for 60 min was used. SASP, pro-inflammatory cytokines and cell cycle mRNAs levels were quantified at 30-min and 72 h post-surgery. Immunohistochemistry in paraffin embedded human brain slides and mouse brain tissue was performed. Our results showed an increase of both p16 and p21 mRNA restricted to the infarct area in the tMCAo brain. Moreover, there was an induction of Il6, Tnfa, Cxc11, and its receptor Cxcr2 mRNA pro-inflammatory cytokines with a high positive correlation with p16/p21 mRNA levels. The p16 was mainly shown in cytoplasm of neurons and cytoplasm/membrane of microglial cells. The p21 was observed in membrane of neurons and also it showed a mixed cytoplasmic and membranous pattern in the microglial cells. In a human stroke patient, an increase of P16 in the perimeter of the MCA infarct area was observed. These suggest a role of SASP in tMCAo mouse model and in human brain tissue. SASP potentially has a physiological role in acute ischemic stroke and neurological function loss.